Implementation of the Team Assisted Individualization (TAI) Learning Model to Improve Learning Outcomes in Volleyball Game Material - Eka Silpiana; Septaliza, Dewi; Martinus, Martinus; Meliyanti, Selvi; Endrawan, I Bagus (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This classroom action research aimed to improve the learning outcomes of fifth-grade students at SD Negeri 2 Merapi Selatan in volleyball passing skills through the implementation of the Team Assisted Individualization (TAI) cooperative learning model. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected using performance tests, observations, and documentation. The findings showed a significant increase in students’ activeness and mastery of basic volleyball techniques, particularly forearm passing. The percentage of students achieving the minimum mastery criteria increased from 65.5% in the pre-cycle to 81.25% in Cycle I, and further to 93.75% in Cycle II. These results indicate that the TAI model not only enhanced students’ technical skills but also fostered collaboration, responsibility, and active participation in the learning process. This study recommends the integration of TAI in Physical Education, Sports, and Health (PJOK) learning to optimize both cognitive and psychomotor outcomes. Future research may explore the application of TAI in other sports disciplines and grade levels to broaden its pedagogical impact.